Does the effectiveness of monetary policy depend on the choice of policy instrument? Empirical evidence from South Korea - Martha Cruz Zuniga; Dawit Senbet (Journal of Central Banking Theory and Practice, 2023)
This study provides robust evidence on how the choice ofthe policy instrument for monetary policy influences its impact oneconomic activity. We study the case of South Korea for the period1980-2017. We use FAVAR models that allow a comprehensive explo-ration of different areas of economic activity by overcoming limita-tions on a number of variables that can be included in the analysisin a traditional VAR model. Following the actual use of instruments,we test the effectiveness of monetary policy in two separate periods:1980-1999, when the Bank of Korea mostly used M2 as the policyinstrument; and then 2000-2017, when interest rate was the policyinstrument. Our results show that monetary policy that uses interestrate as the policy instrument is markedly more effective in economicactivity than M2. This is observable in the reaction from prices aswell as variables that measure industrial production. In contrast, theimpact of M2 mostly occurs in prices and it is short lived. We use ro-bustness checks that switch the use of instrument for each subperiodand also test the use of each policy instrument for the entire periodof analysis. The results hold, interest rates as policy instrument ofmonetary policy are more effective than M2.
Keywords: C55; E52; E58; 330; monetary policy; policy instrument; VAR; FAVAR; impulse response function